Comparative characteristics of drinking water quality standards in some countries - Прибилова, В. М. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
The regulation of drinking water is a complex process that develops and is closely linked with the achievements of science and technology. The formation of valuation (regulation) of drinking water is a long historical process of facts accumulation, their synthesis and interpretation using the achievements of related sciences at the appropriate stage of development. The purpose of this study was a comparative analysis of approaches to the regulation of quality indicators of drinking water in the world and in our country, largely due to the need to harmonize national requirements for drinking water with European and international standards, approaches and numerous proposals for such harmonization.The article provides comparative characteristic standards of drinking water quality in various countries of the world and the EU Directive and estimates the number of monitored indicators of water quality for individual countries in the world. It has been proved that the quality of drinking water can be improved by an integrated solution of some problems, the main of which is the development of new technologies of water treatment and maximum harmonization of the national regulatory framework governing drinking water quality, and standards of the developed countries, particularly the EU and WHO recommendations. Lack of sufficient water resources leads to a deficit in drinking water for the population of these countries. This, in turn, determines the difference between the water supply systems and the capital intensity of the water sector in water scarce regions.